2015
DOI: 10.1371/journal.pone.0135695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Mycobacterium Tuberculosis Complex by 24-Locus Based MIRU-VNTR Typing in Conjunction with Spoligotyping to Assess Genetic Diversity of Strains Circulating in Morocco

Abstract: BackgroundStandard 24-locus Mycobacterial Interspersed Repetitive Unit Variable Number Tandem Repeat (MIRU-VNTR) typing allows to get an improved resolution power for tracing TB transmission and predicting different strain (sub) lineages in a community.MethodologyDuring 2010–2012, a total of 168 Mycobacterium tuberculosis Complex (MTBC) isolates were collected by cluster sampling from 10 different Moroccan cities, and centralized by the National Reference Laboratory of Tuberculosis over the study period. All i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
0
24
2
Order By: Relevance
“…These are the loci previously reported as the most discriminatory in a number of other settings in Iran and elsewhere [10,25–29]. Although the system based on 12 loci is most widely used among different sets of MIRU‐VNTR loci, however, the discriminatory of present study was lower than those of other studies, in which the investigators reported the higher discriminatory yielded by 24 loci MIRU‐VNTR on their isolates [7,13].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…These are the loci previously reported as the most discriminatory in a number of other settings in Iran and elsewhere [10,25–29]. Although the system based on 12 loci is most widely used among different sets of MIRU‐VNTR loci, however, the discriminatory of present study was lower than those of other studies, in which the investigators reported the higher discriminatory yielded by 24 loci MIRU‐VNTR on their isolates [7,13].…”
Section: Discussioncontrasting
confidence: 70%
“…Molecular typing of MTBC is a powerful adjunct to TB control to monitor the disease transmission, and to detect or confirm outbreaks [7]. In last decades, several genotyping methods have been used for studying of molecular epidemiology of MTB.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these regions with a high prevalence of Beijing B0/W148 strains were also reported to have a heavy MDR-TB burden, indicating this closely related group of strains appears to be able to successfully generate resistance to the current standard therapy while they remain transmissible in certain settings [1,46]. Searching through literature, we found these epidemic strains in China were previously also reported in Europe and North Africa but at a low prevalence, suggesting these clusters are globally wide spread but with different levels of adaptation in different areas [47,48]. …”
Section: Discussionmentioning
confidence: 73%
“…Overall, four studies conducted using spoligotyping were included in this review. First, Brudey et al [12] Much later, the study conducted by Bouklata et al [15] has permitted to track and monitor the extent of genetic diversity of MTB strains. Within this context, a total of 168 MTBC isolates were collected during 2010-2012 from 10 different Moroccan cities, and subjected to spoligotyping.…”
Section: Mtb Population Structure Based On Spoligotyping Datamentioning
confidence: 99%